Bottle Versus Syringe Feeding After Palatoplasty: A Systematic Review - Permana, Lucky; Bangun, Kristaninta; Menna, Clara; Amaliah, Rizky (Jurnal Plastik Rekonstruksi, 2024)
Introduction : Postoperative feeding after palatoplasty should be initiated immediately to maintain nutritional intake while preserving the palatal sutures to avoid trauma or tension that can lead to wound rupture. Currently, there is no consensus on post-palatoplasty preferred feeding method. This study aims to compare bottle versus syringe feeding in post-palatoplasty patients.Method : A systematic search was conducted in five databases namely PubMed, Embase, Scopus, ProQuest, and CINAHL, with the following keywords; palatoplasty, cleft palate repair, bottle feeding, syringe feeding, outcome, complication, growth, and nutrition. The selected studies were critically appraised using the Oxford CEBM (Centre for Evidence-Based Medicine) critical appraisal tools.Results: Two studies were included, with a total of 162 subjects. Both studies found that the formation of postoperative wound dehiscence and weight gain did not significantly differ between bottle and syringe groups. However, faster weight gain was observed in the bottle group. Habits and cultural factors could influence the outcomes of these studies.Conclusion: Bottle feeding is not significantly inferior to using syringe in terms of short-term postoperative complications, and can be used as an alternative feeding method for post-palatoplasty patients.